Application of P5BL Model Integrated with Education for Sustainable Development to Develop Motivation and Conceptual Understanding in Science - Tolba, Ehab; Youssef, Nasser Helmy (Jurnal Pendidikan IPA Indonesia, 2026)
Education for sustainable development (ESD) is a priority for modern societies and a central focus of learning. The current study aims to apply the P5BL model, integrated with education for sustainable development, to develop motivation and conceptual understanding in science among middle school students. To achieve the study objectives, a quasi-experimental design was adopted. The research sample comprised 148 students, divided into two groups: an experimental group (76 students) and a control group (72 students). The research tools are a conceptual understanding test and the motivation scale. The results showed statistically significant differences at the 0.01 level between the experimental and control groups' mean scores on the conceptual understanding test after the test, favoring the experimental group (M = 22.32; t = 5.05, p = 0.01, σ² = 0.75). The effect size (d = 3.40) was greater than 0.8 for the test as a whole. Statistically significant differences at the 0.01 level were also found between the experimental and control groups on the overall learning motivation scale, favoring the experimental group (mean = 143.85; t = 21.81, p = 0.01, σ² = 0.87). The effect size (d = 5.15) was greater than 0.8 for the scale as a whole. Therefore, integrating education for sustainable development within the P5BL model not only contributes to the transfer of scientific knowledge but also transforms students from passive recipients into active students with strong intrinsic motivation and the ability to connect scientific concepts to real-world problems and their sustainability. In other words, the P5BL model, integrated with sustainability, successfully transformed the "energy unit" from rigid theoretical content into a practical experience that fostered conceptual understanding (explanation, interpretation, application, and perspective) and increased student motivation (academic ambition, curiosity, independence, challenge, desire to succeed, and self-confidence). Key recommendations include developing guidelines for science teachers to help them teach using the P5BL model integrated with education for sustainable development (ESD) to foster motivation and conceptual understanding, and to integrate P5BL with sustainable development principles and practices into science curriculum instruction. Several research proposals were also presented.